Construction of an EGFP-embedded porcine reproductive and respiratory syndrome virus infectious clone and antiviral drug screening - Liu, Rongxiao; Fu, Shi; Chai, Yukun; Liu, Nian; Liu, Benjin; Luo, Lingzhi; Yang, Wei; Dong, Xiumei; Cui, Jin (Frontiers in Cellular and Infection Microbiology, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV) is a significant pathogen posed a serious threat to the global swine industry. In this study, a BAC-based reverse genetics platform was established using a highly pathogenic PRRSV (HP-PRRSV) strain. Three recombinant reporter viruses were constructed by inserting the enhanced green fluorescent protein (EGFP) gene into three different intergenic regions of the complete PRRSV-L251 genome. Immunofluorescence assays combined with viral growth kinetics and reporter gene stability assessments indicated that rL251-ORF4-5a-EGFP maintained relatively stable expression during serial passage, and viral titers at 72 hours post-infection (hpi) were comparable to the parental virus. Subsequently, we identified four candidate compounds with potential anti-PRRSV activity using rPRRSV-L251-ORF4-5a-EGFP, indicating that this platform can be used as a visual assessment tool for antiviral drug screening. This study demonstrated that the ORF4-5a interval region is a feasible and promising site for exogenous gene insertion, and provided a robust technical platform for PRRSV vaccine development and pathogenesis studies.